Black raspberry extract inhibits regulatory T-cell activity in a murine model of head and neck squamous cell carcinoma chemoprevention - Ryan, Nathan M.; Lamenza, Felipe F.; Upadhaya, Puja; Pracha, Hasan; Springer, Anna; Swingler, Michael; Siddiqui, Arham; Oghumu, Steve (Frontiers in Immunology, 2022)
Head and neck squamous cell carcinomas (HNSCC) are one of the most diagnosed malignancies globally, with a 5-year survival rate of around 40 to 50%. Current therapies are limited to highly invasive surgery, aggressive radiation and chemotherapies. Recent reports have demonstrated the potential phytochemical properties of black raspberries in inhibiting the progression of various cancers including HNSCCs. However, the effects of black raspberry extracts on immune cells of the tumor microenvironment, specifically regulatory T cells during HNSCC have not been investigated. We used a mouse model of 4-nitroquinoline-1-oxide (4NQO) chemically induced HNSCC carcinogenesis to determine these effects. C57BL/6 mice were exposed to 4NQO for 16 weeks and regular water for 8 weeks. 4NQO exposed mice were fed AIN-76A control mouse diet or AIN76 diet supplemented with black raspberry extract. At terminal sacrifice, tumor burdens and immune cell recruitment and activity were analyzed in the tumor microenvironment, draining lymph nodes, and spleens. Mice fed BRB extract supplemented diet displayed decreased tumor burden compared to mice provided AIN-76A control diet. Black raspberry extract administration did not affect overall T cell populations as well as Th1, Th2 or Th17 differentiation in spleens and tumor draining lymph nodes. However, dietary black raspberry extract administration inhibited regulatory T cell recruitment to HNSCC tumor sites. This was associated with an increased cytotoxic immune response in the tumor microenvironment characterized by increased CD8+ T cells and enhanced granzyme B production during BRB extract mediated HNSCC chemoprevention. Interestingly, this enhance CD* T cell antitumoral response was localized at the tumor sites but not at spleens and draining lymph nodes. Furthermore, we found decreased levels of PD-L1 expression by myeloid populations in draining lymph nodes of black raspberry administered carcinogen induced mice. Taken together our findings demonstrate that black raspberry extract inhibits regulatory T cell recruitment and promotes cytotoxic CD8 T cell activity at tumor sites during HNSCC chemoprevention. These results demonstrate the immunomodulatory potential of black raspberry extracts and support the use of black raspberry derived phytochemicals as complementary approach to HNSCC chemoprevention and treatment.